US specificity of occasion setting: hierarchical or configural learning? - Bonardi, Charlotte; Bartle, Craig; Jennings, Domhnall (Elsevier, 2012)
Four experiments in rats examined whether occasion setters and target CSs play qualitatively different roles in occasion-setting discriminations. Two visual occasion setters, A and B, signalled reinforcement of two auditory target CSs, x and y, with sucrose and oil (A…x → suc, B…y → oil, A−, B−, x−, y−); in addition two transfer CSs w and z were paired with sucrose and oil (w → suc, z → oil). When w and z were substituted for x and y (A…w, B…w, A…z, B…z) more responding was observed when both stimuli had been paired with the same outcome (Experiments 1 and 3a). No effect was observed when two visual “pseudo-occasion setters”, C and D (paired with sucrose and oil in a trace relation to the US:C… → suc, D… → oil), were substituted for the occasion setters A and B (C…x, D…x, C…y, D…y; Experiments 2, 3b and 4). These results could not be explained in terms of Pavlovian summation: responding to combinations of Pavlovian CSs paired with same or different outcomes was either the same, or lower when both stimuli had been paired with the same outcome (Experiment 4). Implications of these results for theories of occasion setting and configural learning are discussed.